To the problem of ukrainian-russian relations (on the example of journalism by I. Nechuy-Levytskyi) - Abramova, I. G.; Абрамова, Інна Георгіївна (Одеса : Видавничий дім “Гельветика”, 2022)
Military events in Ukraine, aggression on the part of the Russian state have a clear trend – reinterpretation of Ukrainian-Russian relations through the prism of the work of the famous Ukrainian classicist I. Nechuy-Levytskyi.